2020
DOI: 10.1097/wnr.0000000000001392
|View full text |Cite
|
Sign up to set email alerts
|

Gender impact on transcranial magnetic stimulation-based cortical excitability and cognition relationship in healthy individuals

Abstract: Objective We sought to determine whether cortical excitability, measured via transcranial magnetic stimulation (TMS), is associated with cognition in healthy individuals and whether gender and education have an impact on this relationship. Methods Fifty-four healthy individuals (31 males, mean age = 41.94, SD = 21.98; 23 females, mean age 48.57; SD = 22.84) underwent TMS to assess their resting motor threshold (RMT) and the Repeatable Battery for the As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The reason for such a difference remains unclear and may be explained by the different methods used between the studies. Also, Akilan [ 43 ] attempted to explain the disparity between the RMT as measured by TMS and cognitive function, i.e., MMSE and RBANS scores. However, we found no difference in the mean RMT as 46.06 ± 7.81 in males and 49.96 ± 11.16 SD in females, which are in the normal range as mentioned in our study, 44.31 ± 8.06.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for such a difference remains unclear and may be explained by the different methods used between the studies. Also, Akilan [ 43 ] attempted to explain the disparity between the RMT as measured by TMS and cognitive function, i.e., MMSE and RBANS scores. However, we found no difference in the mean RMT as 46.06 ± 7.81 in males and 49.96 ± 11.16 SD in females, which are in the normal range as mentioned in our study, 44.31 ± 8.06.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with previous research investigating physiological mechanisms of neurological disorders, showing that motor hyperexcitability is related to global cognitive dysfunction ( Takahashi et al, 2013 ; Higashihara et al, 2021 ; Zadey et al, 2021 ) due to increased excitatory activity or/and an inhibitory deficit ( Joseph et al, 2021 ; Meder et al, 2021 ; Mimura et al, 2021 ). Similarly, in healthy subjects, it has been found that hyperexcitability of the motor cortex is associated with impaired attention ( Bolden et al, 2017 ; Akilan et al, 2020 ), suggesting that cortical excitatory and inhibitory balance is necessary for optimal brain and cognitive functioning ( Páscoa dos Santos and Verschure, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very little is present in the literature on this issue, and the few existing pieces of evidence appear somehow contradictory. Schicktanz et al (2014) observed that lower motor cortical excitability was related to better working memory in men ( Schicktanz et al, 2014 ), while Akilan et al (2020) observed that an increase in cortical excitability was related to global cognition in women ( Akilan et al, 2020 ). However, beyond these inconsistencies, which need and deserve deeper study, previous and our results confirm the existence of biological sex differences ( Schicktanz et al, 2014 ; Akilan et al, 2020 ) in the relation between cortical excitability/inhibition and cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations